Demographic histories and genetic diversity across pinnipeds are shaped by human exploitation, ecology and life-history. Issue 1 (December 2018) - Stoffel, M.; Humble, E.; Paijmans, A.; Acevedo-Whitehouse, K.; Chilvers, B.; Dickerson, B.; Galimberti, F.; Gemmell, N.; Goldsworthy, S.; Nichols, H.; Krüger, O.; Negro, S.; et al.
Abstract A central paradigm in conservation biology is that population bottlenecks reduce genetic diversity and population viability. In an era of biodiversity loss and climate change, understanding the determinants and consequences of bottlenecks is therefore an important challenge. However, as most studies focus on single species, the multitude of potential drivers and the consequences of bottlenecks remain elusive. Here, we combined genetic data from over 11, 000 individuals of 30 pinniped species with demographic, ecological and life history data to evaluate the consequences of commercial exploitation by 18th and 19th century sealers. We show that around one third of these species exhibit strong signatures of recent population declines. Bottleneck strength is associated with breeding habitat and mating system variation, and together with global abundance explains much of the variation in genetic diversity across species. Overall, bottleneck intensity is unrelated to IUCN status, although the three most heavily bottlenecked species are endangered. Our study reveals an unforeseen interplay between human exploitation, animal biology, demographic declines and genetic diversity. Historical hunting has caused documented declines in pinnipeds, but the extent to which hunting caused genetic bottlenecks among species was unknown. Here, the authors show evidence of severe bottlenecks in several pinniped species, particularly those that breed on land.